The Impact of Development and Training on the Performance of Faculty at the University: A Field Study at Almaaqal University (Private Sector) - Alrobaie, Ahmed Ismaeel Khedhair (South Asian Journal of Social Sciences and Humanities, 2022)
Training and development are a basic base upon which the effectiveness of the organization rests, and through them, the accumulated experience and knowledge in the workplace is organized and directed towards comprehensive organizational performance. In the field of the university educational process, training and development results in the faculty accumulated knowledge and experience, which in turn improves the level of overall organizational performance at the university level. The structure of the research and its procedures hypothesis that (there is a statistically significant effect (for training and development) on the performance level of faculty at Almaaqal university, and for the purposes of collecting field data, an arbitrator and laboratory questionnaire was used, the study reached an important conclusion that (the positive effect of training and development on the level of performance of faculty at Almaaqal university).
Keywords: Development; Training; Faculty Performance; Almaaqal University